Giant Mature Primary Retroperitoneal Teratoma in a Young Adult: Report of a Rare Case and Literature Review - Walid Sasi; Giuseppe A. Ricchetti; Laila Parvanta; Robert Carpenter (Case Reports in Surgery)
Teratomas are neoplasms of the embryonic tissues that typically arise in the gonadal and sacrococcygeal regions of adults and children. Primary adult retroperitoneal teratomas are rare and demand challenging management options. We report a case of a unilateral primary retroperitoneal mature cystic teratoma mimicking an adrenal mass in a 28-year-old female patient. Complete resection of the mass was performed by a laparotomy approach. Because of the risk of malignancy, follow-up radiographic studies were performed to ensure the oncologic efficacy of resection. The patient remains free of recurrence to date.